2022
DOI: 10.3390/antiox11112198
|View full text |Cite
|
Sign up to set email alerts
|

MnTnHex-2-PyP5+ Displays Anticancer Properties and Enhances Cisplatin Effects in Non-Small Cell Lung Cancer Cells

Abstract: The manganese(III) porphyrin MnTnHex-2-PyP5+ (MnTnHex) is a potent superoxide dismutase mimic and modulator of redox-based transcriptional activity that has been studied in the context of different human disease models, including cancer. Nevertheless, for lung cancer, hardly any information is available. Thus, the present work aims to fill this gap and reports the effects of MnTnHex in non-small cell lung cancer (NSCLC) cells, more specifically, A549 and H1975 cells, in vitro. Both cell lines were initially ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…The anti-migratory effects were more evident/noticeable at the highest tested concentrations of CMBNPs and at longer treatment durations. Several studies also reported different nanoformulations potential abilities to inhibit wound closure and cellular migration in various cancer cell lines [ 22 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The anti-migratory effects were more evident/noticeable at the highest tested concentrations of CMBNPs and at longer treatment durations. Several studies also reported different nanoformulations potential abilities to inhibit wound closure and cellular migration in various cancer cell lines [ 22 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…To select the best NSCLC cell model to study the putative inhibitors, a characterization of the expression of the ERCC1 and ERCC4 (XPF) genes in all cell lines was performed by using quantitative reverse transcription PCR (qRT-PCR), following a previously described protocol [71]. Total RNA was isolated from each cell line (1.0 × 10 6 cells/sample) using TRIzol™ Reagent (Invitrogen™, Waltham, MA, USA) and extracted according to the manufacturer's instructions.…”
Section: Gene Expressionmentioning
confidence: 99%
“…Antioxidant enzyme mimetics are compounds that mimic the function of antioxidant enzymes, protecting cells from OS. Several trials are underway or have been completed to evaluate the efficacy of antioxidant enzyme mimetics [ [251] , [252] , [253] , [254] ]. For example, GC4419 is an investigational SOD mimetic drug that is being developed to protect normal tissues from radiation-induced oral mucositis and enhance the radiation therapy effect in patients with head and neck cancer (NCT03689712).…”
Section: Strategies For Enhancing Antitumor Effects Of Drug-induced O...mentioning
confidence: 99%